Pengaruh Konsumsi Daun Kacang Panjang Terhadap Peningkatan Kadar Hemoglobin Pada Ibu Hamil Tm Ii Dengan Anemia Di Wilayah Kerja Puskesmas Polanharjo Kabupaten Klaten - Dewi Andang Prastika; Onny Setiani; Sri Sumarni (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Long Bean Leaves, Haemoglobin, Pregnancy Second Trimester. Anemia in pregnancy is called the 'potencial danger of mother and child' because anemia is a serious problem and need attention from all parties involved in maternal and child health services. WHO reported that the prevalence of anemia in pregnancy in the world amounted to 55% and tended to increase with increasing gestational age. To determine the effect of bean leaf consumption to increased hemoglobin levels of second trimester- pregnant women with anemia in Puskesmas Polanharjo working area. This research was Quasy experiment with a pretest posttest control group design. This research used a treatment group is the group of second trimester-pregnant women with anemia has given long bean leaves consumption as many as 15 respondents and the control group is the group of pregnant women with anemia second trimester without additional Fe tablet intake as many as 15 respondents. There is a difference between the average of hemoglobin levels before the intervention group consumed long beans leaves with an average of hemoglobin levels in the intervention group after consuming long beans leaves. By eating 350 grams of long beans leaves for one month (28 days) may help prevent anemia in pregnant women.